Rice Productivity and Water Use Efficiency under Different Irrigation Management System in North-Western India - Kaur, Mahekpreet; Sharma, Karamjit (Indian Journal of Extension Education, 2022)
Rice (Oryza sativa L.) is an important kharif cereal crop with huge irrigation water demand. Over the years, several water saving technologies have been developed, tested and disseminated among farming community for enhancing irrigation water productivity in rice. The present study, compared continuous flooding (T1), alternate wetting and drying in which irrigation is done 2 days after seepage (AWD; T2), soil matric potential (ψm;tensiometer guided) based irrigation scheduling at ψm=15kPa (T3) and ψm=20kPa (T4) using PAU tensiometer on basmati rice (var. Pusa Basamti-1121) productivity and water use efficiency (WUE). The results revealed significantly (p
Keywords: Alternate wetting and drying; Basmati rice yield; PAU Tensiometer; Water use efficiency